Comparison of the human and mouse erythropoietin genes shows extensive homology in the flanking regions. - Galson, D; Tan, C; Ratcliffe, P; Bunn, H (1993)
Considerable insights into important cis regulatory elements in a gene can be gleaned from the identification of sequence homologies among different species. To extend and optimize the sequence comparison between human and mouse erythropoietin (Epo) genes, we have obtained new human sequence from 5,547 to 385 bp upstream of the cap site and extended the 3' flank by 489 bp. In addition, we have obtained new sequence information on the mouse Epo gene extending from within the 3' untranslated region (UTR) to 1,001 bp downstream of the polyadenylation site. Analysis of these additional sequences shows considerable homology between human and mouse Epo genes as far as 4 kb (human) or 3 kb (mouse) upstream of the cap sites, as well as far more homology at the 3' end than was previously realized. In addition, both species were found to have a high frequency of short interspersed (SINE) repetitive sequences that interrupt homologies in both the 5' flank and within the transcription unit.